Nanogenerator-based hybrid systems for smart textiles - Nguyen-Tri, Phuong; Nguyen, Tuan Anh; Ehrmann, Andrea (Nanosensors and Nanodevices for Smart Multifunctional Textiles)
The integration of smart devices and materials in the textiles for cutting-edge technologies applications is very promising research direction. The nanogenerator refers to the use of the nanoscale devices and nanomaterials to convert various kinds of energies dealing with thermal, light, and mechanical to electricity for specific applications. This research direction is new and remains still various open question from the fundamental aspects (principles, mechanism, fundamental theories, mathematical equation, and simulation) and practical points of view (design, preparation methods, functionality, efficiency, and durability). In this chapter, we briefly introduce about the nanogenerators, especially flexible/wearable nanogenerators that are used in textiles fields. Some fundamental aspects relating to the design, preparation, and connection of piezoelectric and triboelectric nanogenerators with discussion on the main advantages and drawbacks are addressed. We then present the last update on the combination of nanogenerator with other devices such as flexible batteries, solar cells, and other wearable energy systems to form hybrid system. A conclusion with a prospective development of these materials will be introduced at the end of this chapter.